2020
DOI: 10.3390/app10217490
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Extracellular DNA and DNase Activity in Periodontitis

Abstract: Extracellular DNA (ecDNA) is a potential marker and predictor in several inflammatory diseases. Periodontitis, a chronic inflammatory disease, is associated with epithelial cell death and could lead to release of DNA. Our aim was to analyze salivary DNA concentration and deoxyribonuclease (DNase) activity in periodontitis patients. We hypothesized that salivary ecDNA will be higher than in controls and could serve as a marker of periodontitis severity. Samples of saliva were collected from 25 patients with chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…In using calculated S p to improve the use of UVGI in reducing the transmission of disease, a sense of the ranges of measured concentrations of UV-absorbing molecules such as nucleic acids can be beneficial. Konec̆ná et al (2020) reported average dsDNA concentrations in whole saliva of 0.24 g/l in healthy subjects and 0.5 g/L in persons with periodontitis. However, in the supernatants from centrifuged (1600× g ) samples they measured average concentrations of DNA of 0.054 g/l in healthy subjects and 0.07 g/l in persons with periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…In using calculated S p to improve the use of UVGI in reducing the transmission of disease, a sense of the ranges of measured concentrations of UV-absorbing molecules such as nucleic acids can be beneficial. Konec̆ná et al (2020) reported average dsDNA concentrations in whole saliva of 0.24 g/l in healthy subjects and 0.5 g/L in persons with periodontitis. However, in the supernatants from centrifuged (1600× g ) samples they measured average concentrations of DNA of 0.054 g/l in healthy subjects and 0.07 g/l in persons with periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…DNases are a group of enzymes that hydrolyze cfDNA, allowing its removal from the body fluids. It could be possible that the incorrect functioning of the salivary DNases is another reason why the cfDNA level increases in periodontitis [ 79 ]. It was seen that periodontal bacteria could influence the activities of DNases [ 80 ].…”
Section: Cfdna and Periodontitismentioning
confidence: 99%
“…This study did not show differences in the activity of DNases between patients affected by periodontitis and healthy patients. These results could be linked to the fact that the samplings were frozen and stored [ 79 ]. Therefore, it is not yet clear whether there is a correlation with cfDNA concentration.…”
Section: Cfdna and Periodontitismentioning
confidence: 99%
See 1 more Smart Citation
“…In using calculated S p to improve the use of UVGI in reducing the transmission of disease, a sense of the ranges of measured concentrations of UV-absorbing molecules such as nucleic acids can be beneficial. Konec n et al (2020) reported average dsDNA concentrations in whole saliva of 0.24 g/l in healthy subjects and 0.5 g/L in persons with periodontitis. In supernatants from centrifuged (1600× g) samples they measured average concentrations of DNA of 0.054 g/l in healthy subjects and 0.07 g/l in persons with periodontitis.…”
Section: Uncertaintiesmentioning
confidence: 99%